Effectiveness of Windmill-Blowing Play Therapy on the Respiratory Status of Toddlers with Bronchopneumonia - Hanifa Farinda; Nur Eni Lestari; Isti Anindya (Poltekkes Kemenkes Banjarmasin, 2026)
Bronchopneumonia is one of the leading causes of respiratory problems in toddlers. Non-pharmacological interventions such as breathing exercises may help improve pulmonary ventilation and oxygenation. One approach that can be implemented is windmill-blowing play therapy, which adopts the Pursed Lips Breathing (PLB) technique and may enhance children’s participation during breathing exercises. This study aimed to examine the effect of windmill-blowing play therapy on respiratory status and the degree of respiratory distress in toddlers with bronchopneumonia. This study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. A total of 30 toddlers diagnosed with bronchopneumonia were selected using purposive sampling. The intervention consisted of windmill-blowing play therapy incorporating the Pursed Lips Breathing technique. The measured parameters included respiratory rate, pulse rate, oxygen saturation, and the degree of respiratory distress. Data were analyzed using the Wilcoxon Test. The results demonstrated a significant reduction in respiratory rate from a mean of 52 to 37 breaths per minute (p < 0.001), a decrease in pulse rate from 150 to 124 beats per minute (p < 0.001), and an improvement in oxygen saturation from 89.50% to 96.00% (p < 0.001). The score of respiratory distress also decreased significantly from 14.90 to 6.87 (p < 0.001). Windmill-blowing play therapy showed a significant effect in improving respiratory status and reducing the degree of respiratory distress in toddlers with bronchopneumonia.